Preparation, Structural Analysis, and Reactivity Studies of Phosphenium Dications - Tay, Madelyn Qin Yi (2016)
This work expands on the recent synthesis and reactivity of the two-coordinate P(III)-containing dication [((Ph3P)2C)P(NiPr2)]2+ (3a2+). Two additional dications of general formula [((RPh2P)2C)P(NR′2)]2+ (3b2+, R = 1/2 (CH2)3, R′ = iPr; 3c2+, R = Ph, R′ = Cy) have been prepared. Solution and solid-state 31P NMR isotropic shifts for this dication class were observed around 360 ppm. Except for [3a][SbF6]2, the 31P CP/MAS NMR spectra reveal a high degree of structural disorder around the dicationic site in the solid state. Surprisingly, the synthesis of dication 3a2+ was only possible in the presence of AlCl4–, SbF6–, and substituted tetraarylborates, while the use of ClO4–, OTf–, BF4–, PF6–, and BPh4– resulted in complex product mixtures. Single-crystal X-ray analysis of dications 3a2+ and 3c2+ suggested a 4π allyl-like structure for the central CPN fragment, and this has been supported through detailed theoretical investigations. Initial reactivity studies between dications 3a2+/3c2+ and PMe3 show an equilibrium between the free dication and the target adduct. Furthermore, 3a2+ has been shown to be capable of O–H bond activation using water and methanol and polymerizes THF when it is dissolved in this solvent